2021
DOI: 10.1017/wet.2021.99
|View full text |Cite
|
Sign up to set email alerts
|

Critical timing of weed removal in dry bean as influenced by the use of preemergence herbicides

Abstract: The critical timing of weed removal (CTWR) is the point in crop development when weed control must be initiated to prevent crop yield loss due to weed competition. A field study was conducted in 2018 and 2020 near Scottsbluff, NE to determine how the use of preemergence herbicides impacts the CTWR in dry bean. The experiment was arranged as a split-plot, with herbicide treatment and weed removal timing as main and sub plot factors, respectively. Herbicide treatment consisted of no-preemergence, or pendimethali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…As a rule, herbicide applications are recommended at the early stages of crop growth and development, or even before the seedlings' emergence because weeds at the early stages of their development are more susceptible to herbicides. Moreover, modern ideas concerning the planning of protective measures are based on the concept of critical timing of weed removal (CTWR) when treatments need to be applied to prevent yield decrease due to competition between the crop and weed plants (Nedeljković et al, 2021;Beiermann et al, 2022;Soltani et al, 2022). As a result, developmental stages have been established for each crop when they were routinely treated with herbicides.…”
Section: Extension Of Application Periodmentioning
confidence: 99%
“…As a rule, herbicide applications are recommended at the early stages of crop growth and development, or even before the seedlings' emergence because weeds at the early stages of their development are more susceptible to herbicides. Moreover, modern ideas concerning the planning of protective measures are based on the concept of critical timing of weed removal (CTWR) when treatments need to be applied to prevent yield decrease due to competition between the crop and weed plants (Nedeljković et al, 2021;Beiermann et al, 2022;Soltani et al, 2022). As a result, developmental stages have been established for each crop when they were routinely treated with herbicides.…”
Section: Extension Of Application Periodmentioning
confidence: 99%
“…By comparison, a 50% yield loss would be expected in corn and soybean without effective weed control (Soltani et al 2016(Soltani et al , 2017a. Beiermann et al (2022b) found dry bean yield to be reduced by 82% to 97% in western Nebraska when weeds were allowed to compete with dry bean.…”
Section: Introductionmentioning
confidence: 99%
“…Soil organic carbon (SOC) includes plants, roots, fungi, and microbial residues and accounts for more than 60% of global total soil carbon [1]. The understanding of weed-removal practices, including herbicides application and mulching, which affect soil carbon balance dynamics, is crucial for yield-potential preservation, terrestrial ecosystem conservation, and food security [2,3]. Sustainable weed management constitutes a challenge for ensuring agricultural productivity since in the case of improper management, infestations of grass and broadleaf weeds could reduce crops yield and quality.…”
Section: Introductionmentioning
confidence: 99%